High respiratory rate is associated with early reduction of lung edema clearance in an experimental model of ARDS. Issue 1 (10th August 2015) - Retamal, J.; Borges, J. B.; Bruhn, A.; Cao, X.; Feinstein, R.; Hedenstierna, G.; Johansson, S.; Suarez‐Sipmann, F.; Larsson, A.
Abstract : Background: The independent impact of respiratory rate on ventilator‐induced lung injury has not been fully elucidated. The aim of this study was to investigate the effects of two clinically relevant respiratory rates on early ventilator‐induced lung injury evolution and lung edema during the protective ARDSNet strategy. We hypothesized that the use of a higher respiratory rate during a protective ARDSNet ventilation strategy increases lung inflammation and, in addition, lung edema associated to strain‐induced activation of transforming growth factor beta (TGF‐β) in the lung epithelium. Methods: Twelve healthy piglets were submitted to a two‐hit lung injury model and randomized into two groups: LRR (20 breaths/min) and HRR (40 breaths/min). They were mechanically ventilated during 6 h according to the ARDSNet strategy. We assessed respiratory mechanics, hemodynamics, and extravascular lung water (EVLW). At the end of the experiment, the lungs were excised and wet/dry ratio, TGF‐β pathway markers, regional histology, and cytokines were evaluated. Results: No differences in oxygenation, PaCO2 levels, systemic and pulmonary arterial pressures were observed during the study. Respiratory system compliance and mean airway pressure were lower in LRR group. A decrease in EVLW over time occurred only in the LRR group ( P < 0.05). Wet/dry ratio was higher in the HRR group ( P < 0.05), as well as TGF‐β pathway activation. Histological findings suggestive of inflammation and inflammatory tissue cytokines were higher in LRR. Conclusion: HRR was associated with more pulmonary edema and higher activation of the TGF‐β pathway. In contrast with our hypothesis, HRR was associated with less lung inflammation.